Efeitos de uma sessão de realidade virtual sobre o equilíbrio dos indivíduos tabagistas - Amaral, Marciele Dulor (2019)
To assess the body balance and verify the effects of virtual reality on smokers. This is a descriptive case series study involving six smokers evaluated throught the dynamic computerized posturography by using Balance Manager from Neurocom Internation Inc, and subsequentely submitted to a single virtual reality session with Xbox 360 videogame including the Kinect sensor. After this session, the participants were reavaluated by posturography. Initially it was used descriptive statistics for data analysis. To describe the balance variables description it was used the mean values and standard deviation. To describe the environment influence the distribuition was symmetrical and it was used the mean and standard deviation, as well as the Sudent’s t test and Pearson correlation. For all analyzes, a level significance of 5% was used. Among the 6 smokers evaluated, anyone has presented a balance deficit statistically significant, however, two smokers showed vestibular system problems, which it was compensated by the other systems. After the virtual reality session, Composite has improved, but it was not statistically significant. Therefore, there was a statiscally significance improvement at the vestibular system (p=0,04). Conclusion: The virtual reality may be a useful tool at the smokers and non-smokers balance problems treatment. However, this tool should be study as a complementary technique to treat cardiopulmonar and vestibular system problems.